Perempuan dalam Kungkungan Budaya Politik Patriarkhis - Nurbaity Prastyananda Yuwono (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2018)
Women's political participation in Indonesia can be categorized as low, even though the government has provided special policies for women. Patriarchal political culture is a major obstacle in increasing women's political participation, because it builds perceptions that women are inappropriate, unsuitable and unfit to engage in the political domain. The notion that women are more appropriate in the domestic area; identified politics are masculine, so women are not suitable for acting in the political domain; Weak women and not having the ability to become leaders, are the result of the construction of a patriarchal political culture. Efforts must be doing to increase women's participation, i.e: women's political awareness, gender-based political education; building and strengthening relationships between women's networks and organizations; attract qualified women political party cadres; cultural reconstruction and reinterpretation of religious understanding that is gender biased; movement to change the organizational structure of political parties and; the implementation of legislation effectively.